2021
DOI: 10.1039/d0na01008a
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and nano-encapsulated metal and alloy-based phase-change materials for thermal energy storage

Abstract: A new class of phase change materials based on encapsulated metal and alloy micro- and nano-particles with advanced thermophysical properties for cyclable and stable thermal energy storage/release is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 109 publications
(208 reference statements)
0
8
0
Order By: Relevance
“…Inorganic PCMs have advantages of large phase-change latent heat and non-flammability . However, two major problems of supercooling and phase separation limit their applications . Organic PCMs have thereby gained widespread attention due to their low supercooling, high chemical stability, and non-corrosiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic PCMs have advantages of large phase-change latent heat and non-flammability . However, two major problems of supercooling and phase separation limit their applications . Organic PCMs have thereby gained widespread attention due to their low supercooling, high chemical stability, and non-corrosiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 26 provided a detailed review of the numerous ways for microencapsulating PCMs with a wide temperature range in a variety of organic and inorganic shell materials. Zhu et al 27 focused on a review of micro‐ and nano‐encapsulation of metal and alloy PCMs with low‐ to high‐melting temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The organic PCMs are represented by paraffins, fatty acids, esters and polymers, which have the characteristics of high latent heat per unit mass, low thermal conductivity, and large volume change between solid and liquid states, while the inorganic PCMs mainly include molten salts, hydrated salts and metal. 1,2 Metal PCMs have attracted much attention in recent years, due to their outstanding advantages in high thermal conductivity, high latent heat per unit volume and small volume change before and aer phase change. 2,3 In particular, the value of low melting point metal or so called "liquid metal" represented by gallium in passive thermal management has long been reported, 4,5 and some recent studies also demonstrated its potential in thermoregulation and aerospace.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Metal PCMs have attracted much attention in recent years, due to their outstanding advantages in high thermal conductivity, high latent heat per unit volume and small volume change before and aer phase change. 2,3 In particular, the value of low melting point metal or so called "liquid metal" represented by gallium in passive thermal management has long been reported, 4,5 and some recent studies also demonstrated its potential in thermoregulation and aerospace. 6,7 The advantages and disadvantages of the above PCMs are very clear.…”
Section: Introductionmentioning
confidence: 99%